2002
DOI: 10.1111/j.1559-1816.2002.tb00263.x
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of Self‐Reports of Condom Use and Sexual Behavior

Abstract: In a study of the accuracy of self‐reports of sexual behavior and condom use, 285 single, young adults in a large metropolitan area were interviewed once a week for 52 weeks, reporting on their sexual behavior each week. At 1‐, 3‐, 6‐, and 12‐month intervals, the individuals also provided self‐reports of the number of times they had engaged in sex and the number of times they had used condoms since they began participating in the study. These self‐reports were compared with aggregates of the weekly data, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(93 citation statements)
references
References 38 publications
3
90
0
Order By: Relevance
“…Our findings do suggest that the daily diary recall is a useful tool for both methodological as well as substantive questions related to sexual and substance use behaviors. Although implementing diary recalls in a study protocol requires time and effort for both the investigator as well as the participants, similar to work by Jaccard et al (2002), participants in this study completed the diaries conscientiously with few missing data. Effect sizes of common psychological predictors of accuracy (i.e., conscientiousness, depression, substance use, social desirability) were small and may, therefore, have limited impact on recall accuracy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings do suggest that the daily diary recall is a useful tool for both methodological as well as substantive questions related to sexual and substance use behaviors. Although implementing diary recalls in a study protocol requires time and effort for both the investigator as well as the participants, similar to work by Jaccard et al (2002), participants in this study completed the diaries conscientiously with few missing data. Effect sizes of common psychological predictors of accuracy (i.e., conscientiousness, depression, substance use, social desirability) were small and may, therefore, have limited impact on recall accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that sexual behaviors can be recalled consistently for intervals of 1-3 months (Carey, Carey, Maisto, Gordon, and Weinhardt, 2001;Graham et al, 2003;Jaccard et al, 2002). Longer time frames may be more representative of a person's sexual behavior patterns, but can be more difficult to recall.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The accuracy of self-reports, as an indicator of consistent condom use, has been questioned (de Visser & Smith, 2000;Turner & Miller, 1997;Weir, Roddy, Zekeng, & Ryan, 1999) but others (Ajzen & Fishbein, 2004;Jaccard, McDonald, Wan, Dittus, & Quinlan, 2002;Morris, 1993) have found self-reported measures reasonably accurate. Furthermore, in most cases, self-report remains one of a few feasible data collection methods for intimate sexual behaviors barring direct observation.…”
Section: Limitationsmentioning
confidence: 99%
“…Schroder et al (2003) argued that count data are preferable for evaluation studies, whereas measures of relative condom use, such as the measures used in this study, are preferable for etiological and correlational research. Experiments that have compared diary reports with retrospections of up to a year find that retrospective recall of condom use is very accurate (Graham, Catania, Brand, Duong, & Canchola, 2003;Jaccard, McDonald, Wan, Dittus, & Quinlan, 2002). …”
Section: Author Manuscriptmentioning
confidence: 99%